PENDIDIKAN DALAM HIMPITAN KAPITALISME: : TINJAUAN KRITIS ATAS PERAN LEMBAGA PENDIDIKAN DAN POSISIONALITAS GURU - Batlayeri, Willem (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2015)
This article is meant to be a critical reflection on the ideal responsibility of educational institutions and the role of the teachers in today’s world of education. The article focuses on the problem of the declining morality of the education as a result of the hegemony of global capitalism. This becomes apparent in the spreading of the culture of industrialisation and commercialisation of education. The moment has come to reflect seriously on the genuine culture, so as to build a new paradigma in matters of education, especially by reconstructing the ideal role and responsibility and the reposition of the role of the teachers, specifically the catholic teachers of religion in the world of education. To this end, as a base of analysis on the above mentioned matters, in this article some critical thoughts in matters of culture will be the base of analysis.